O4: A NOVEL BOWEL DISEASE MODEL: PHENOTYPIC DIVERSITY OF CONTROL VS FAP ORGANOIDS. (27th April 2021) - Martin, I; Wu, Y; Patel, R; Kalra, P; K, S Clark; von, A Roon; Latchford, A; Moore, JG
Abstract: Introduction: The lifetime risk of colorectal cancer in familial adenomatous polyposis (FAP) approaches 100%. In patients who have undergone prophylactic colectomy, duodenal cancer is 100‐300 times more common than in the general population, and an important cause of death. We aimed to develop in vitro models of mucosal crypt‐derived organoids from patients with FAP. Method: Biopsies from apparent healthy duodenal mucosa of FAP patients undergoing upper gastrointestinal endoscopy or surgery yielded crypts that were immobilised in Matrigel Basement Membrane Matrix (Corning) and cultured in IntestiCult Organoid Growth Medium (StemCell Technologies) to generate organoids for further morphologic and immunocytochemistry analyses (Dako and Abcam antibodies). Result: Duodenal crypt‐derived organoids from one healthy volunteer formed ring structures (days 1 ‐2) that progressed to expected branched structures (days 4‐7). FAP‐derived organoids from 9 patients all generated organoids with aberrant morphologies. These organoids expressed markers of Paneth cells (lysozyme), proliferation (Ki‐67), goblet cells (Muc‐2) and the single cell layer of mucosal epithelium (CK18). Conclusion: This is the first report of duodenal crypt‐derived organoids generated from FAP patients. Aberrant organoid morphologies were observed in all 9 patients. Immunocytochemistry confirmed markers of duodenal epithelium, suggesting a promising in vitro model to study disease aetiology in FAP. Take‐home message: This is a step towards a personalised model of disease for patients with familial adenomatous polyposis.